FUNCIONALIDADE FAMILIAR DE IDOSOS EM UM CENTRO GERIÁTRICO FILANTRÓPICO DE SALVADOR-BA - Reis, Jackson Santos dos; Dias, Ewerton Naves; Castro, Carlos Henrique Rodrigues; Tessarolo , Mariana Medeiros Mota; Santos, Hugo Raphael Carvalhaes; Santos, Raíla Alves Dos; Silva, Janaína Almeida (Periódicos Brasil. Pesquisa Científica, 2026)
Background: Population aging has increased the demand for healthcare services to address not only clinical conditions but also relational dimensions such as family functioning, which plays a central role in the care of older adults. Family dysfunction is associated with adverse outcomes, including poor treatment adherence, psychological distress, and institutionalization. Objective: To evaluate family functioning among older adults attending a philanthropic geriatric center in an urban area of Salvador, Brazil, and to describe their sociodemographic and clinical profile. Methods: This is a quantitative, observational, cross-sectional study conducted with 69 individuals aged 60 years or older. A convenience sampling method was used. Data collection included a sociodemographic and health questionnaire and the Family APGAR instrument. Family functioning was analyzed at the item level, without calculating total scores or performing inferential statistical analysis. Descriptive statistics were used to summarize the data. Results: The sample was predominantly female (85.5%), with a high prevalence of retirement (92.8%), multimorbidity (78.3%), and low physical activity (94.2%). Most participants had no partner (88.4%) but reported having children (89.9%) and active family support (73.9%). Responses to the Family APGAR items were predominantly positive, including the ability to rely on family (76.8%), communication and problem sharing (72.5%), support for decision-making (76.8%), expressions of affection (76.8%), and shared time (81.2%). Conclusions: Despite a profile indicating high care demands, participants reported favorable perceptions of family functioning, suggesting the presence of adaptive family support mechanisms. Assessing family functioning at the item level may provide practical insights for healthcare teams, enabling early identification of vulnerabilities and guiding targeted interventions in geriatric care.